Compact Dielectric Elastomer Linear Actuators. (4th September 2018) - Zhao, Huichan; Hussain, Aftab M.; Duduta, Mihai; Vogt, Daniel M.; Wood, Robert J.; Clarke, David R.
Abstract: The design and fabrication of a rolled dielectric elastomer actuator is described and the parametric dependence of the displacement and blocked force on the actuator geometry, elastomer layer thickness, voltage, and number of turns is analyzed. Combinations of different elastomers and carbon nanotube electrodes are investigated and optimized to meet performance characteristics appropriate to tactile display applications, namely operation up to 200 Hz with a combination of a 1 N blocked force and free displacement of 1 mm, all within a volume of less than 1 cm 3 . Lives in excess of 50 000 cycles have been obtained. Key to meeting these objectives is control of the multilayering fabrication process, the carbon nanotube electrode concentration, the selection of a soft elastomer with low viscous losses, and a proof‐testing procedure for enhancing life cycle reliability. Abstract : A flexible manufacturing approach based on multilayering elastomers and carbon nanotube electrodes followed by rolling is proposed. Combinations of different elastomers, carbon nanotube electrodes, and geometries are investigated analytically and experimentally and optimized to meet performance characteristics appropriate to tactile display applications in both static mode and dynamic mode.